Strategi Marketing Mix Klinik Paradise Parisudha Desa Sumberagung Plosoklaten Kediri dalam Meningkatkan Volume Penjualan - Nuzula, Sayda Firdausi; Fauza, Nilna; Shidiqy, Dhiya’u (Al-Muraqabah: Journal of Management and Sharia Business, 2024)
This study aims to analyze the marketing mix strategy used by the Paradise Parisudha Clinic in increasing the sales volume of their skin care products. This research uses a qualitative approach with primary data obtained through interviews and direct observation, as well as secondary data which includes sales reports, customer files, and related books. The results of this study show that Klinik Paradise Parisudha effectively implements all elements of the 7P marketing mix, including product, price, distribution, promotion, people, process, and physical evidence. However, this study also found that the product element became the most successful marketing strategy in increasing the sales of Paradise Parisudha Clinic. This may indicate that it is important to produce attractive and quality products to attract customers and increase sales. In conclusion, Klinik Paradise Parisudha has successfully implemented a comprehensive marketing mix strategy, with an emphasis on products, to increase their sales volume in the competitive beauty clinic industry.